A CONTRASTIVE STUDY OF THE FUNCTIONAL AND CULTURAL ROLES OF STAGE PROPS IN ENGLISH AND UZBEK THEATRE - Dinora Ibodullayeva Bahramjanovna; Uralova Oysuluv Payanovna (Western European Studies, 2025)
This paper explores the artistic, functional, and cultural significance of stage props in English and Uzbek theatre. While English theatre has developed standardized systems of stage prop design and symbolism through semiotic and technical traditions, Uzbek theatre integrates props as cultural and historical markers reflecting national identity. The research applies a contrastive analysis to identify similarities and differences in the use and meaning of props, drawing on semiotic, descriptive, and comparative methods
Keywords: stage props; theatre semiotics; cultural identity